Control of salmonella rissen and staphylococcus aureus in fermented beef sausage by a combination of cinnamon and mace oils - Nanasombat, Suree; Wimuttigosol, Pornpan (My University, 2012)
The antibacterial effect of cinnamon and mace oils on different food model media was evaluated. All pathogenic bacteria tested (Salmonella Senftenberg, Salmonella Rissen, Staphylococcus aureus and Listeria monocytogenes) were sensitive to cinnamon oil on sausage agar (0.063 mg.mL-1 minimum inhibitory concentrations; MIC), but the spoilage bacterium, Pseudomonas fluorescens was susceptible to this oil on meat agar (0.015 mg.mL-1 MIC). However, S. Rissen was the most resistant bacterium to mace oil on sausage agar (22 mg.mL-1 MIC). Most of the lactic acid bacteria tested (Pediococcus pentosaceus, Lactococcus lactis, Enterococcus faecalis and Enterococcus faecium) were more resistant to mace oil as compared to cinnamon oil. Then, the effect of mixed cinnamon and mace oils at different concentrations on the survival of S. Rissen and Staph. aureus in fermented beef sausages was studied. A cinnamon (1,008 ppm) and mace (1,375 ppm) oil combination effectively decreased Staph. aureus viable counts in fermented beef sausages by 3.70 log CFU.g-1 at the end of fermentation (96 h). However, cinnamon oil (252 ppm) with mace oil (1,375 ppm) was sufficient to decrease viable S. Rissen cells to below detection level (less than 1 log CFU.g-1) in fermented sausages.
Keywords: Cinnamon oil; Fermented meat; Mace oil; Salmonella; Staphylococcus aureus